A country scale analysis revealed effective forest policy affecting forest cover changes in Cambodia. (June 2020) - Ota, Tetsuji; Lonn, Pichdara; Mizoue, Nobuya
Highlights: Community forest, protected areas and protected forest decreased deforestation. Effectiveness for forest conservation varies depending on the approach. The authority managing the approach has an important influence on effectiveness. Abstract: Considerable proportions of the remaining global forest areas are currently harboured in tropical countries. Reducing deforestation in this region is important to help mitigate climate change. Effective forest conservation approach is needed to reduce deforestation and degradation in these countries. Here, we investigated the forest conservation effect of community forests and protected areas using country scale data in Cambodia. In addition to these two forest conservation approaches, we also evaluated the effectiveness of protected forests, which are similar to protected areas but managed by different authorities. We compared deforestation between 2006 and 2016 in areas under the three forest conservation approaches and a non-conserved area by applying the inverse probability of treatment weighting with the propensity score minimizing confounding effects. The results showed that community forest, protected areas, and protected forest significantly decreased deforestation compared with non-conserved forests. Out of the three forest conservation approaches, protected forest was the most effective and community forest was the least effective. We conclude that all of the policies we evaluated are effective for forest conservation but the effectiveness varies depending on the approach. Our findings also suggest that the authority managing the given approach plays an important part in its effectiveness.